The Role of HKBP Church in Preserving Batak Cultural Identity Among the Young Generation of Batak Christians (Case Study of HKBP Cinta Damai Church) - Agustry Vernando Simamora, Rocky; Marhaeni Munthe, Hadriana; Sitorus, Henri; Badaruddin, Badaruddin; Simanihuruk, Muba (CV. Green Publisher Indonesia, 2024)
In the relationship between religion and culture, there are institutions that have legitimacy to overshadow both, one of which is religious institutions. Huria Kristen Batak Protestant (HKBP) as one of the religious institutions is seen as a place of spiritual fellowship and cultural fellowship (Batak) that has legitimacy to preserve. This preservation departs from the phenomenon of fading Batak cultural identity among the Young Generation of Batak Christians today in the midst of hybrid culture is an interesting thing to research. This research is a case study using qualitative methods with the aim of explaining the role of HKBP Church in efforts to preserve Batak Cultural Identity Among the Young Generation of Batak Christians with a Case Study of HKBP Cinta Damai Church. The results showed that HKBP became a place of spiritual and cultural communion based on the historical history of the cultural journey of the HKBP Church. However, the mixing of cultures (hybrid) due to the times makes the Batak Christian Young Generation have no interest in their identity besides the parental factor that does not inherit. Social Construction The role of HKBP Cinta Damai Church in preserving Batak Cultural Identity in building social practices received a positive response and interest from the Young Generation of Batak Christians